Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10278-012-9515-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Variability in the Assessment of Digital Chest X-ray Image Quality

Abstract: A large database of digital chest radiographs was developed over a 14-month period. Ten radiographic technologists and five radiologists independently evaluated a stratified subset of images from the database for quality deficiencies and decided whether each image should be rejected. The evaluation results showed that the radiographic technologists and radiologists agreed only moderately in their assessments. When compared against each other, radiologist and technologist reader groups were found to have even l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The prevalence of positioning errors as well as the considerable variation in radiographer reject rates indicates that the standards of image quality within the department may not be consistent. This is a common finding in the literature . A study by Dunn and Rogers found that radiologists are typically more lenient with image quality, accepting 50% of images that radiographers rejected due to positioning errors.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The prevalence of positioning errors as well as the considerable variation in radiographer reject rates indicates that the standards of image quality within the department may not be consistent. This is a common finding in the literature . A study by Dunn and Rogers found that radiologists are typically more lenient with image quality, accepting 50% of images that radiographers rejected due to positioning errors.…”
Section: Discussionmentioning
confidence: 88%
“…This is a common finding in the literature. 6,7,16 A study by Dunn and Rogers 6 found that radiologists are typically more lenient with image quality, accepting 50% of images that radiographers rejected due to positioning errors. Likewise, a study by Nol et al 10 suggested that one reason positioning error has become more common is due to the reduction in communication regarding image quality between radiologists and radiographers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the introduction of Picture Archiving and Communication System (PACS) the interaction and communication between radiographers and radiologists have been significantly reduced (18), culminating in tele-radiological services. This trend has intensified the high variability of image quality perception observed both between radiologists (19) and especially between radiologists and radiographers (20). Thus it could be shown that radiologists agreed only in 60% of cases with the necessity to retake a chest posterior anterior (PA) x-ray radiograph, that had been previously rejected by the radiographers (21).…”
Section: Introductionmentioning
confidence: 99%